Use of a Single-Strand Specific Nuclease for Analysis of Bacterial and Plasmid Deoxyribonucleic Acid Homo- and Heteroduplexes - Crosa, Jorge H. (1973)
Bacterial and plasmid homo- and heteroduplexes have been analyzed with a single-strand specific endonuclease, S1, of Aspergillus oryzae. Under appropriate assay conditions, there was a high degree of correlation between the degree of deoxyribonucleic acid (DNA)-DNA homoduplex formation assessed by the S1 endonuclease and by hydroxyapatite (HA). Heteroduplexes which contain extensive regions of polynucleotide sequences in common are similarly recognized by the S1 endonuclease and HA. In instances where there is little or imperfect complementarity between heterologous DNA strands, the S1 endonuclease and the HA method give slightly different estimates. From DNA duplex thermal stability experiments assayed with the S1 endonuclease, there is preliminary evidence that well-matched sequences identified by the enzyme are not similarly recognized by HA. The assay of homo- and heteroduplexes with the S1 endonuclease permits an accurate, reproducible and rapid determination of polynucleotide sequence relationships and may be seriously considered as a method of choice for survey work and for investigations which require a large number of DNA-DNA hybridization assays.